Saluran Air Tertutup sebagai Faktor Penekan Populasi Tikus di Daerah Bekas Fokus Pes Cangkringan Sleman Yogyakarta - Sukismanto Sukismanto; Lupita Chairunnisa; Indah Werdiningsih (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2017)
Sub-district Cangkringan of Sleman District is an focus area of Plague surveillance at the slopes of Merapi Mountains. Eruption montains was interested alert of rats to insert surrounding villages mountain. Surveillance such as monitoring of rats population was doing for early warning Plague and other disease such as Leptospirosis disease. Sub-district Cangkringan consist of five villages, Wukirsari village is one of former focus. The purpose of study was to determine home environment conditions contributed to trap success. Study design was observational with cross sectional, size of sample as 66 samples (home). Data analyzed with univariat and bivariate. The number of rats caught in the village of Wukirsari are 36 rats with 27.7% trap success with type of rats by Rattus rattus diardi with number of “Xenopsylla cheopis” are 5. Index flea was calculated of 0.13. based on bivariat analysis just closed water channel variabel was significantly correlated with trap success.